Interactivity, the heart and soul of effective learning: The interlink between internet self-efficacy and the creation of an inclusive learning experience - Dlamini, R. (South African Journal of Higher Education, 2023)
There is a growing recognition that the relationship between digital technologies and education is more complex and multi-faceted than previously conceived. Given the multi-faceted nature of digital education, which involves social and technology elements in the realm of knowledge-acquisition, an epistemic community such as a community of inquiry (CoI) provides an appropriate theoretical perspective to frame the analysis of the interlink between internet self-efficacy and inclusive learning experiences. In recognition of the importance of active participation in the ubiquitous learning environment, the argument focused on the development of a CoI as an intellectual community that provides a structure for educators to implement digital education. Central to this article is the development of the various presences to sustain interaction and reflection in a socio-epistemological orientation approach. Notwithstanding the widely recognised affordances of digital technologies to connect people, this study was conducted to elicit relevant evidence on digital education, to gain insights into the practicality of digital education, to articulate several important research questions within each of the identified affordances, and to provide suggestions for institutions pursuing digital education. Furthermore, there is clear evidence that digital education is intertwined with digital capital and digital inclusion.